The Petrie Museum of Egyptian Archaeology: Characters and Collections (2015)
The Petrie Museum of Egyptian Archaeology ﬁrst opened its doors in 1915, and since then has attracted visitors from all over the world as well as providing valuable teaching resources. Named after its founder, the pioneering archaeologist Flinders Petrie, the Museum holds more than 80,000 objects and is one of the largest and finest collections of Egyptian and Sudanese archaeology in the world. Richly illustrated and engagingly written, the book moves back and forth between recent history and the ancient past, between objects and people. Experts discuss the discovery, history and care of key objects in the collections such as the Koptos lions and Roman era panel portraits. The rich and varied history of the Petrie Museum is revealed by the secrets that sit on its shelves.